Capital tax competition with heterogeneous firms and agglomeration effects - John Burbidge; Katherine Cuff; John Leach (Center for Economic Studies and ifo Institute (CESifo), 2004)
Our paper extends the capital tax competition literature by incorporating heterogeneous capital and agglomeration. Our model nests the standard tax competition model as well as the special case in which there is agglomeration but no firm/capital heterogeneity and the opposite case, firm heterogeneity with no agglomeration. We build on the existing tax competition literature as well as establish a link between this literature and the more recent work on agglomeration using the new economic geography model. Our main contribution lies in allowing for firm heterogeneity which we show plays a role similar to decreasing returns in regional production.
Keywords: H70; H32; R38; 330; tax competition; heterogeneous firms; agglomeration; Kapitalertragsteuer; Steuerwettbewerb; Agglomerationseffekt; Neue ökonomische Geographie; Theorie